2022
DOI: 10.3390/jcm11071871
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Perinatal and Neonatal Outcomes of Triplet Pregnancies According to Chorionicity: A Systematic Review of the Literature and Meta-Analysis

Abstract: Triplet pregnancies are rare events that affect approximately 93 in 100,000 deliveries in the world, especially due to the increased use of assisted reproductive techniques and older maternal age. Triplet pregnancies are associated with a higher risk of fetal and maternal morbidity and mortality compared to twins and singletons. Chorionicity has been proposed as a major determinant of perinatal and maternal outcomes in triplet pregnancies, although further evidence is needed to clarify the extent and real infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
15
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 75 publications
(112 reference statements)
10
15
5
Order By: Relevance
“…27 In addition, monochorionic and dichorionic triplet pregnancies were almost twice as likely to have NICU admissions, respiratory distress, sepsis, and necrotizing enterocolitis compared with trichorionic triplets. 26 Interestingly, in the absence of TTTS, neonatal mortality is not affected by chorionicity. 27…”
Section: Outcomes Based On Chorionicitymentioning
confidence: 99%
See 2 more Smart Citations
“…27 In addition, monochorionic and dichorionic triplet pregnancies were almost twice as likely to have NICU admissions, respiratory distress, sepsis, and necrotizing enterocolitis compared with trichorionic triplets. 26 Interestingly, in the absence of TTTS, neonatal mortality is not affected by chorionicity. 27…”
Section: Outcomes Based On Chorionicitymentioning
confidence: 99%
“…Monochorionic triplets are rare, with estimated incidence of 1/100,000 births. 25 A meta-analysis found that monochorionic and dichorionic triplet pregnancies were more likely to have intrauterine fetal demise compared with trichorionic triplet pregnancies, 26 likely due to the previously mentioned complications of a shared placenta. Monochorionic and dichorionic triplet pregnancies are more likely to be delivered at earlier gestational ages (< 30 wk gestation) and have lower birthweight neonates compared with trichorionic triplets.…”
Section: Outcomes Based On Chorionicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Triplet pregnancies are considered high-risk pregnancies due to the associated maternal, fetal, perinatal and neonatal morbidity, compared with twin and singleton pregnancies. In fact, the rates of preterm birth, premature rupture of membranes, restricted intrauterine growth, prematurity and low birth weight are notably high, as well as those of neonatal complications associated with prematurity [ 12 , 13 , 14 , 15 , 16 , 17 ]. In our setting, Revello published a study in 2019 describing the prevalence of maternal and obstetric complications in triplet pregnancies from their experience in another tertiary hospital in our city, where the most frequently observed obstetric complication in triplet pregnancies overall is the threat of preterm labor (56%), premature rupture of membranes (28.9%) and preeclampsia (20.4%) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address the global effect of chorionicity on the morbidity and mortality of triplet pregnancies, our research group recently carried out a systematic review and meta-analysis of the literature published during the last 15 years and observed that non-trichorionic pregnancies had a higher risk of admission to the NICU, respiratory distress, sepsis, necrotizing enterocolitis and perinatal and intrauterine mortality [ 16 ]. This systematic review and meta-analysis included multiple hospitals in various countries and continents to obtain a sample that would allow us to observe significant associations among variables in such a rare obstetric event with such an impact on morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%